Rapid and sustained contact tracing training for COVID-19 in San Francisco: a training model for developing an emergency public health workforce - Martin, Shayanne; Kalra, Anika; Jenny, Alisa; Maher, Andrew D.; Foreman, Allison; Chavez, Alejandro; Gagliano, Jayne; Reid, Michael J. A.; Brickley, Debbie Bain (Frontiers in Public Health, 2023)
The City and County of San Francisco was the first municipality in the United States to institute a COVID-19 contact tracing program. The San Francisco Department of Public Health (SFDPH) and the University of California, San Francisco (UCSF) created an outcome-based fully remote contact tracing curriculum using participatory learning methods to train non-public health emergency workers as contact tracers. Between April and December 2020, we trained over 300 individuals in contact tracing skills and procedures over three training phases. Using iterative curriculum design and Kirkpatrick’s evaluation methodology, we aimed to ensure high quality and successful person-centered contact tracing. The resulting curriculum consisted of 24 learning outcomes taught with six participatory skills development activities, asynchronous materials, and one-on-one contact tracer support. We collected more than 700 responses from trainees using various evaluation tools across the training phases, and contact tracers interviewed more than 24,000 contacts after training in our program. Our evaluations showed that knowledge and skills improved for most trainees and demonstrated the utility of the training program in preparing trainees to perform person-centered contact tracing in San Francisco. Local health jurisdictions and state health agencies can use this model of curriculum development and evaluation to rapidly train a non-public health workforce to respond to future public health emergencies.